Vitamin D status differs by sex, sport-season, and skin pigmentation among elite collegiate basketball players - Fields, J. B.; Payne, D. C.; Gallo, S.; Busteed, D. R.; Jones, M. T. (Sports, 2019)
Vitamin D plays a key role in bone health, musculoskeletal function, and sport performance. Collegiate athletes competing in indoor sports may be at greater risk of vitamin D deficiency due to limited outdoor time. Therefore, the purpose was to assess 25-hydroxyvitamin D (25(OH)D) concentrations among collegiate men and women basketball (MBB, WBB) athletes. National Collegiate Athletic Association Division I men (MBB, n = 11) and women (WBB, n = 9) were tested during the off-season (T1; July) and pre-season (T2; October). Measurements included serum 25(OH)D; skin pigmentation, bone mineral density, and daily sun exposure (self-reported). Paired t-tests determined changes in 25(OH)D by sport-season and sex. Pearson correlations examined relationships between outcome variables. MBB athletes (mean ± SD; 19.6 ± 1.3 years) showed a reduction in 25(OH)D (T1: 64.53 nmol·L-1 ± 11.96) (T2: 56.11 nmol·L-1 ± 7.90) (p = 0.001). WBB (20.1 ± 1.1 years) had no change in 25(OH)D (T1: 99.07 nmol·L-1 ± 49.94. T2: 97.56 nmol·L-1 ± 36.47, p = 0.848). A positive association between 25(OH)D and skin pigmentation was observed (r = 0.47, p = 0.038). 25(OH)D was inversely correlated with lean body mass (LBM), body mass (BM), and bone mineral density (BMD), while a positive association was seen between 25(OH)D and skin pigmentation. In summary, 25(OH)D insufficiency was prevalent amongst male collegiate basketball athletes, with 25(OH)D levels being lower in the pre-season (October) than the off-season (July). Furthermore, darker skin pigmentation significantly correlated with 25(OH)D, indicating that individuals with darker skin tones may be at a greater risk of insufficiency/deficiency. More research is needed to examine the relationships between 25(OH)D and bone health in athletes.